Confucianism Ethic and the Spirit of Capitalism - Usman, Usman (DINIKA : Academic Journal of Islamic Studies, 2016)
This article tries to explore the fundamental values of Confucianism ethics and its influence to the emergence of Capitalism. By using Weber's thesis on the relationship between Protestant ethics and the spirit of capitalism, this paper concludes that the three important values of Confucianism Ethics (ren: benevolence, humaneness, li: rightness, righteousness, and fittingness, and yi: rules of proper conduct, ritual, and rites) are proposing people on how to become good human beings. If the Confucian follows these ethics properly, he/she will get the successful life. Although it is not guaranteed but the Confucianism ethics are still relevant to be practiced in contemporary situation. Some research findings recently showed that Confucianism ethics have really influence people to fulfill the "calling" (Weber's term) and it has also power to increase the spirit of capitalism. The rise of Japan, China, and the four little dragons (including South Korea, Taiwan, Hong Kong, and Singapore) is related to the development of Confucianism, and it directly brings down Weber's view point, which taught that Confucianism did not have the spirit of capitalism.